2015
DOI: 10.1080/1359432x.2014.996554
|View full text |Cite
|
Sign up to set email alerts
|

That’s not my place: The interacting effects of faultlines, subgroup size, and social competence on social loafing behaviour in work groups

Abstract: Taking a social relations approach to team diversity, we propose that faultlines-hypothetical dividing lines that split a team into relatively homogeneous subgroups-impact the team members' propensity to exhibit social loafing behaviour. We further propose that this individual-level reaction to the faultline structure of the team can differ among team members, depending on the size of their subgroup and on their individual social competence. We tested the assumptions with a sample of real teams working on an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 114 publications
0
36
0
1
Order By: Relevance
“…Moreover, we found one study that examined the moderating effect of social competence. Meyer, Schermuly, and Kauffeld () showed that social competence buffers against the negative effects of faultlines on social loafing behavior in work groups.…”
Section: What Moderates the Effects Of Workplace Diversity?mentioning
confidence: 99%
“…Moreover, we found one study that examined the moderating effect of social competence. Meyer, Schermuly, and Kauffeld () showed that social competence buffers against the negative effects of faultlines on social loafing behavior in work groups.…”
Section: What Moderates the Effects Of Workplace Diversity?mentioning
confidence: 99%
“…Recent theory on within‐team coordination and performance (Crawford and LePine, ) suggests that the core process through which individual team members coordinate and perform is the formation and maintenance of task‐ and teamwork ties that facilitate coordination and exchange. Importantly, prior research has shown that team diversity impacts the formation of within‐team network ties (Reagans et al, ) and that faultlines prevent the formation of network ties between members of different subgroups (Mäs et al, ; see also Meyer et al, ).…”
Section: Faultlines Subgroups and Individual Performancementioning
confidence: 99%
“…Thus, if faultlines impact the formation of task and teamwork ties (Crawford and LePine, ; Mäs et al, ), they are also likely to affect individual team members' cognitions. For example, members of teams that are characterized by a strong faultline are likely to exhibit an increased level of social loafing, but to different extents, depending on differences in subgroup characteristics (Meyer et al, ). These arguments suggest that faultlines can negatively impact individual team member performance by affecting individual access to team knowledge and resources and by affecting individual team members' cognitive states.…”
Section: Faultlines Subgroups and Individual Performancementioning
confidence: 99%
“…However, the subgroups that are created by faultline splits within a team have different properties, such as different sizes and different informational resources, that create a unique level of interdependence within a given subgroup (Carton & Cummings, 2012;2013). Accordingly, one study found that members of larger subgroups are more likely to exhibit social loafing behavior, especially if they displayed low levels of social competence (Meyer, Schermuly, & Kauffeld, 2016). Similarly, members of homogeneous subgroups that include the leader of the team perform better than members of leaderless subgroups if the organization faces a crisis (Meyer, Shemla, Li, & Wegge, 2015).…”
Section: Subgroup-level Dynamics In Diverse Teamsmentioning
confidence: 99%